2016
DOI: 10.1016/j.ijscr.2016.07.039
|View full text |Cite
|
Sign up to set email alerts
|

The ALPPS procedure for hepatocellular carcinoma larger than 10 centimeters

Abstract: HighlightsThe options of treatment for hepatocellular carcinoma are presented.Treatment of huge hepatocellular carcinoma by ALPPS is proposal.Better results with ALPPS for hepatocellular carcinoma than other palliative procedures are discussed.Selection of patients with huge hepatocellular for ALPPS to achieve good results is important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Remarkable hypertrophy has been observed in ALPPS for HCC, even in patients with low-grade fibrosis. [21][22][23] In order to minimise the impact of the first stage, some authors have suggested a combination of hanging manoeuvre and anterior approach in cirrhotic patients. This procedure seems to be better performed by robotic approach than laparoscopically and is associated with reduced blood loss and minimal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkable hypertrophy has been observed in ALPPS for HCC, even in patients with low-grade fibrosis. [21][22][23] In order to minimise the impact of the first stage, some authors have suggested a combination of hanging manoeuvre and anterior approach in cirrhotic patients. This procedure seems to be better performed by robotic approach than laparoscopically and is associated with reduced blood loss and minimal morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure seems to be better performed by robotic approach than laparoscopically and is associated with reduced blood loss and minimal morbidity and mortality. [21][22][23] Schadde et al observed that MELD score over 10 before stage-2 is an independent predictor of 90-day mortality, in addition to previously defined risk factors. The disease-free at 1 year was 87% and 90-day mortality was 12%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available evidence indicates the incidence of morbidity and mortality is high among HCC and IHCC patients treated using ALPPS [ 26 , 27 , 38 , 49 , 50 , 52 , 54 , 57 , 58 , 69 , 70 ]. In the first edition of the ALPPS World Registry [ 37 ], the 90-day mortality was reported to be 9%, but it was higher for HCC (12%), IHCC (13%), perihiliar cholangiocarcinoma (27%) and gallbladder carcinoma (33%) than in cases of colorectal liver metastasis (CRLM) (8%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore ALPPS for huge HCC has been reported without an increased risk of morbidity or mortality (10). In the reported case, a multimodal therapy was the winning strategy.…”
Section: Introductionmentioning
confidence: 87%